Involvement of School Committee in Budgeting Control: A Case Study at Primary School Bani Hasyim Malang Indonesia - Yoyok Amirudin; Jainudin; Zobi Mazhabi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research objective to discuss how the involvement school committee in budgeting control. In the private school some of the financial was came from parents. Parent is the primary teacher’s partner to collaborate the school programs. They were join in the school committee to catch on the school budgeting. The education system obligated schools to report the school budgeting upon approval school committee. The research subject consisted of understanding the role policy of school committee and how far the school committee involve in the budgeting control. This research design was field research with a descriptive qualitative approach. The data has been collected by interviewed teachers, school principal and school committee. The result showed that school committee in Bani Hasyim primary school Malang Indonesia involved in budgeting control. The involvement of parents is not only limited to coming to school for drop out and pick up their children, but also parents share the opinions, gives feedback and suggestions for the sustainability of the school, especially in school budgeting activities and school activities. The school committee was very active in planning and budgeting discussion with the school periodically, once every three months and once a year. In addition, school committees are also involved in monitoring and evaluating school budgets.